Elaboración de una guía turística digital del cantón Quilanga, provincia de Loja - González Castillo, Andrea Michelle (2023)
The present titling and research work called: "Elaboration of a digital tourist guide of the Quilanga canton, province of Loja", this project proposed as its general objective to elaborate the digital tourist guide of the Quilanga canton, likewise, in this project, they were planned three specific objectives: Diagnose the tourist potential of the Quilanga Canton; Design the digital tourist guide for the Quilanga canton, And prepare the dissemination plan for the digital tourist guide of the Quilanga canton. For the development of this research project, specific information was collected from primary and secondary academic and digital documentary sources. In addition, some technical visits were carried out and at the same time the Carla Ricaurte methodology and the MINTUR attractiveness ranking sheets were used; on the other hand, surveys were applied to potential demand and the most relevant actors in the canton's tourism sector were interviewed, the manual for the creation of a digital destination guide prepared by the Smart Destinations Network (DTI) was also used as a methodology. ), in addition, a matrix of the marketing strategy and a dissemination plan for each dissemination channel were prepared. As a result, the canton's digital tourist guide was obtained in interactive pdf format and its dissemination plan. In this way, the conclusions were given and it was established that the digital tourist guide allowed clear and concise information on the attractions and tourist services of the Quilanga canton. Regarding the recommendations, they were addressed to the Cantonal Decentralized Autonomous Government for the use and dissemination of the guide, and the updating of the cadaster.